PENYUSUNAN LAPORAN KEUANGAN PADA USAHA KECIL DAN MENENGAH (UKM) BERDASARKAN SAK ETAP (Studi Pada UKM Meubel Hamida) - B1032131031, SUPRIADI (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
This study is a qualitative study using a case study approach is intended to implement and prepare financial statements on SMEsÂ  Meubel Hamida in the year of 2015 based the Financial Accounting Standards Entities Without Public Accountability (SAK ETAP). In the process of collecting data using interviews and documentation techniques conducted on SMEs Meubel Hamida. Results from this study showed that SMEs Meubel Hamida did not yet make financial statements in accordance the Financial Accounting Standards Entities Without Public Accountability (SAK ETAP). SMEs Meubel Hamida only provides reports of receipts and disbursements during one the period and the causes of SMEs Meubel Hamida did not yet make financial statements in accordance with SAK ETAP is the lack of knowledge about the preparation of financial statements according to the standard and limited human resources. The preparation of financial statements in SMEs Meubel Hamida in the year of 2015 has been collated and adapted to the Financial Accounting Standards Entities Without Public Accountability (SAK ETAP), which consists of (a) Statement of Financial Position / Balance Sheet, (b) profit / loss statement, (c) Report Changes in Equity, (d) Statements of Cash Flows, and (e) Notes to the Financial Statements. Keywords: Financial Statement, SAK ETAP, SMEs